Knowledge Overview of Home Environmental Sanitation Of Stunting Toddler In Pakis Village, Sawahan District, Surabaya City - Sulistyorini, Lilis; Azizah, R.; Arfiani, Novi Dian; Mukono, J.; Keman, Soedjajadi; Yudhastuti, Ririh; Sudarmaji, Sudarmaji; Adriyani, Retno; Prasasti, Corie Indria; Lusno, Muhammad Farid Dimjati; Lestari, Kusuma Scorpia; Diyanah, Khuliyah Candraning; Pawitra, Aditya Sukma; Husnina, Zida; Dwiyanti, Endang; Rizaldi, M Addin; Agustin, Avita Fitri; Izdihar, Hana’ (ABDIMAYUDA: Indonesian Journal of Community Empowerment for Health, 2024)
Stunting in children under five is a global health problem that can be influenced by various factors, including inadequate home sanitation. Stunting in children can be chronic from environmental sanitation problems, infectious diseases, and lack of food consumption. The contribution of poor home environmental sanitation to the problem of stunting can be seen from the growth of disease-causing microorganisms that can cause infections in the body, so that children experience growth failure. Pakis Village, as the partner area of this program, is part of the working area of Puskesmas Pakis Surabaya. Stunting in Pakis Village is still a serious problem because it is one of the villages with a high incidence of stunting in Surabaya City in 2022. This community service activity contributes to further understanding of the description of home sanitation and the incidence of stunting in toddlers. Community service is carried out in the form of home environmental sanitation counseling in supporting the elimination of stunting in infants and toddlers. Participants in the Community Service counseling were 26 participants out of 30 pre-test average results of participants who knew about home environmental sanitation which was 67.63 then after counseling / education related to home environmental sanitation there was an increase of 20.38% or the average post test score was 81.41. Cooperation between the government, community, and harvesters is needed.